Alternative rational technique to compute multi-objective linear programming problems - Abbas al-Bayati; Basim Hassan; baraat sulayman (College of Education for Pure Sciences, 2012)
Abstract In this paper, we have been suggested an alterative rational technique to compute the value of the objective function of a multi-objective linear programming problems. Numerical results indicate that the efficiency of our proposed technique corresponding to standard Chandra Sen method is very effective according to a number of selected test problems.